From Corpus to Junior Dictionary: An Example of the Balinese Language - Praminatih, Gusti Ayu (Jurnal Kajian Bali (Journal of Bali Studies); Vol 13 No 1 (2023): Volume 13 No 1 April 2023DO - 10.24843/JKB.2023.v13.i01.p03, 2023)
Corpus has significantly contributed to dictionary-making. However, despite this high potential, scholars need to pay more attention to the benefits of corpus to junior dictionary development of Indonesia’s local language, i.e., the Balinese language. To fill this gap, the researcher built a 56590 word-sized corpus from the data obtained from published Balinese short stories and children’s songs. AntCont version 4.1.1 software was employed to retrieve words and collocations, focusing on selecting nouns for the junior dictionary entries. The study was the first of its kind to utilise corpus to design a junior dictionary for the Balinese language. Theoretically, this study significantly improved the design of a new corpus-based dictionary for junior users that entails unique and culturally bound words in Balinese. Practically, this study expands the number of dictionaries provided as a source for learning Balinese, primarily for junior users.